She always wore red eaudiobook Fairlawn series, book 2. - Hunt, Angela (Fairlawn, 2008)
Angela Hunt's compelling sequel to her Christy Award nominee Doesn't She Look Natural? delivers a revealing look at friendship and family, life and death. Now living in the Victorian funeral home she inherited, Jennifer struggles to rebuild her post-divorce life in Florida. But when this busy mother, mortuary student, and embalmer's apprentice learns her new friend's true identity, her faith is severely tested.